Elongation method for electronic structure calculations of random DNA sequences. Issue 28 (4th September 2015) - Orimoto, Yuuichi; Liu, Kai; Aoki, Yuriko
<x xml:space="preserve">Abstract</x> We applied ab initio order‐N elongation (ELG) method to calculate electronic structures of various deoxyribonucleic acid (DNA) models. We aim to test potential application of the method for building a database of DNA electronic structures. The ELG method mimics polymerization reactions on a computer and meets the requirements for linear scaling computational efficiency and high accuracy, even for huge systems. As a benchmark test, we applied the method for calculations of various types of random sequenced A‐ and B‐type DNA models with and without counterions. In each case, the ELG method maintained high accuracy with small errors in energy on the order of 10−8 hartree/atom compared with conventional calculations. We demonstrate that the ELG method can provide valuable information such as stabilization energies and local densities of states for each DNA sequence. In addition, we discuss the "restarting" feature of the ELG method for constructing a database that exhaustively covers DNA species. © 2015 Wiley Periodicals, Inc.